Isolation of some thermophylic and acid-resistant Actinomyces strains biosynthesizing cellulase from pineapple waste - Chinh, Tang Thi; Ninh, Tran Ha; Dung, Hoang Thi (Academia Journal of Biology, 2014)
Nowadays, in Vietnam, the pineapple cultivation surface reached 32,000 ha with 1.5 millions of pineapple fruit tones per year. In Vietnam, had been built 9 pineapple canneries and 6 pineapple juice factories, but most of them hadn’t got technology for the solid waste and wastewater treatments, so their wastes always polluted the environmental areas. Three thermophylic Actinomyces strains D5, D6 and D7 having high capacity to produce cellulase in the medium with pH = 4 were isolated from the pineapple waste. They could grow and synthesize cellulase with the incubation temperature from 25oC to 60oC and the optimum temperatures for their growth and their cellulase production were from 45oC to 50oC whith the pH = 5. They grown well in the media containing saccharose and starch as carbon sources and organic nitrogen sourses such as meat extract and peptone. But their highest cellulase production was in the media containing cellulose or CMC-Na as carbon sources and potassium nitrate as nitrogen source. They could not grow and produce cellulase in the media containing ammonium sulfate as nitrogen source. So, these three Actinomyces strains could grow in the media whith pH = 4 and at high temperature. They will be used to make micro-organic product to treat the pineapple solid waste.